The effective oxidation state of a peatland. Issue 1 (15th January 2016) - Worrall, Fred; Clay, Gareth D.; Moody, Catherine S.; Burt, Tim P.; Rose, Rob
Abstract: The oxidative ratio (OR) of the organic matter of the terrestrial biosphere is a key parameter in the understanding of the magnitude of the carbon sink represented both by the terrestrial biosphere and by the global oceans. However, no study has considered the oxidation state of all the organic pools and fluxes within one environment. In this study all organic matter pathways (dissolved organic matter, particulate organic matter, CO2, and CH4 ) were measured within an upland peat ecosystem in northern England. The study showed the following: (1) The peat soil of ecosystem was accumulating oxygen at a rate of between −16 and −73 t O km −2  yr −1 ; (2) Although there was no significant variation in oxidation state in the peat profile, there was a significant increase in degree of unsaturation with depth; (3) The dissolved organic matter leaving the ecosystem was significantly more oxidized than the other carbon pools analyzed while the particulate organic matter was not significantly different from the peat soil profile; and (4) Assuming that all carbon flux from the site was as CO2, the OR of the ecosystem was 1.07; when the nature and speciation of the release pathways were considered, the ecosystem OR was 1.04. At the global scale, correcting for the speciation of carbon fluxes means that the annual global fluxes of carbon to land = 1.49 ± 0.003 Gt C/yr and to the oceans = 2.01 ± 0.004 Gt C/yr. Key Points: First time oxidation state is considered for all carbon pools in a single ecosystem Shows the relative oxidation states of the terrestrial organic matter We can provide an estimate of global terrestrial sinks including fluvial fluxes